1996
DOI: 10.1046/j.1365-2265.1996.7630779.x
|View full text |Cite
|
Sign up to set email alerts
|

Megaoesophagus in a patient with autoimmune polyglandular syndrome Type II

Abstract: Dysphagia and vomiting are frequently present in untreated Addison's disease. These non-specific symptoms may be due either to the metabolic disorder and myopathy or to disorders associated with Addison's disease. We describe a patient with autoimmune adrenal failure as a feature of autoimmune polyglandular syndrome (APS) type II. This patient was referred initially because of megaoesophagus. The association of megaoesophagus with Addison's disease or any of the three types of APS has not previously been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
(10 reference statements)
1
18
0
Order By: Relevance
“…One other case of PAS type II associated with megaesophagus has been reported in a human [3], and similar to our patient that case had positive adrenal and thyroid autoantibodies. However, our patient had both manometry and barium esophagogram studies consistent with achalasia, while manometry studies in the previously reported case were inconsistent with achalasia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One other case of PAS type II associated with megaesophagus has been reported in a human [3], and similar to our patient that case had positive adrenal and thyroid autoantibodies. However, our patient had both manometry and barium esophagogram studies consistent with achalasia, while manometry studies in the previously reported case were inconsistent with achalasia.…”
Section: Discussionsupporting
confidence: 90%
“…Conceivable pathologies which would cause combined esophageal motility disorders and hypoadrenalism include amyloidosis, malignant infiltration of the esophagus and adrenal gland, adrenoleukodystrophy and Allgrove syndrome [3]. In our patient, histology of the esophageal biopsy specimens had excluded amyloidosis and malignancy.…”
Section: Discussionmentioning
confidence: 89%
“…These disorders include Sjögren's syndrome (MIM 270150) (Koivukangas et al 1973;Poglio et al 2007;Simila et al 1978;Weissmann 1958), autoimmune polyglandular syndrome (APS) type 2 (MIM 269200) (Fritzen et al 1996), autoimmune thyropathies (Emami et al 2007;Kroupa et al 2008), and sarcoidosis (MIM 181000).…”
Section: Other Syndromes and Diseasesmentioning
confidence: 99%
“…Adrenal dysfunction is described in association with achalasia (Allgrove syndrome) characterised by a combination of achalasia, adrenal deficiency, and alacrima which is known to have an autosomal recessive pattern of inheritance. 4 A variety of autoimmune conditions have been described in association with achalasia autoimmune polyglandular syndrome, 5 Myasthenia gravis and polymyositis. 6 Anti Myenteric plexus antibodies have been demonstrated in cases of achalasia 7,8 which makes autoimmunity a plausible hypothesis.…”
Section: Discussionmentioning
confidence: 99%